Aquatic therapy in population groups of economically vulnerable adults as a strategy for health prevention - Rodríguez Ramírez, Grettel (2025)
The present opinion article intends to disseminate the work being carried out by the project ED 3532 Aquatic therapy in economically vulnerable adults for health prevention, which promotes health and the treatment of osteo-muscular injuries in vulnerable populations, via Aquatic Therapy interventions at the Hydrotherapy Laboratory of the School of Health Technologies of Universidad de Costa Rica (UCR). Health promotion is one of the contributions UCR makes to Costa Rican society, and this project has offered this contribution for the last three years through the aforementioned interventions. This strategy of non-pharmacological treatment involves several benefits for this kind of population, and that is why spaces such as this are relevant and should be more widely promoted in the different bodies dealing with public health.